Automata, Languages, and Programming 41st International Colloquium, ICALP 2014, Copenhagen, Denmark, July 8-11, 2014, Proceedings, Part I - Esparza, Javier; Fraigniaud, Pierre; Husfeldt, Thore; Koutsoupias, Elias (Theoretical Computer Science and General Issues,, 2014)
This two-volume set of LNCS 8572 and LNCS 8573 constitutes the refereed proceedings of the 41st International Colloquium on Automata, Languages and Programming, ICALP 2014, held in Copenhagen, Denmark, in July 2014. The total of 136 revised full papers presented together with 4 invited talks were carefully reviewed and selected from 484 submissions. The papers are organized in three tracks focussing on Algorithms, Complexity, and Games, Logic, Semantics, Automata, and Theory of Programming, Foundations of Networked Computation.